The Effect of Multimedia Utilization on Increasing Students Learning Outcomes - Salome Rajagukguk; Asmina Herawaty Sinaga; Fenny Mustika Piliang; Alfian Tanjung; Asmayani (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of using multimedia on improving student learning outcomes on excretory system material in class XI SMA YPK Pematangsiantar. The total population of 64 people consisting of 2 classes and samples were taken by random assignment so that 2 classes were obtained, namely the control class (XI-3) 32 people and the experimental class (XI-1) 32 people. The control class was treated without using multimedia power point and the experimental class was treated using multimedia power point. Data analysis was carried out by finding the average (, standard deviation (S) and hypothesis testing (t test) at the significance level = 0.05. From the results of the study, the averageÂ post-test for the control class was 88 and the experimental class was 90.13 with a difference in learning outcomes of 2.13. From the results of hypothesis testing (t test) obtained tcount (2.790) > ttable (1.99) at a significance level of 0.05 and degrees of freedom (dk) = 62, then Ho rejected and Hais accepted, meaning that there is an effect of using multimedia power point to improve student learning outcomes on the material of the human excretory system in class XI SMA YPK Pematangsiantar. It was concluded that there was an effect of using multimedia on improving student learning outcomes in the material of the human excretory system of class XI SMA YPK Pematangsiantar.